The Effect of Current Ratio, Total Asset Turnover and Net Profit Margin on Profit Growth in the Companies Listed on The Indonesia Stock Exchange - Lusia Nensilya Octavia Lero; Sri Hermuningsih; Risal Rinofah (Borong Newinera Publisher, 2024)
This study seeks to investigate the impact of Currency Ratio, total asset turnover, and net margin profile on profit growth in banking firms listed on the Indonesia Stock Exchange from 2018 to 2022. This study involves quantitative analysis based on secondary data collected from financial reports of banking companies listed on the Indonesia Stock Exchange for a period of 5 years. The data in this study was analyzed using SPSS Statistics version 21. This research unveils that the current ratio positively impacts profit growth, while total asset turnover also affects profit growth. Net profile margin positively impacts profit growth, and there is a simultaneous positive relationship with current ratios. Examining the impact of total asset turnover and net margin profile on the profit growth of companies listed on the Indonesia Stock Exchange.